An Analysis of Politeness Strategies Used by The Teacher and Students in a Multicultural Class - ., LUH GEDE MAYA WIRASTUTI DEWI; ., PROF. DR. I KETUT SEKEN, M.A.; ., PROF. DR. I NYM. ADI JAYA PUTRA, M.A. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2016)
This study aimed at investigating teacher?s politeness strategies in four teacher?s roles and analyzing students? politeness strategies. The object of this descriptive qualitative research was utterances delivered by teacher and students in the class discussions. The instrument of the study was the researcher who collected data through observation and interview. The data were gained by observing and video-recording classroom discussions, identifying the politeness strategies used, and classifying the politeness strategies found. The gained data were then analyzed qualitatively through data reduction, data display, and conclusion. In this study, the data were displayed on tables and interpreted through excerpts of conversations in the classroom discussions. It was found that there were 496 teacher?s utterances related to politeness strategies. Bald on record was the most prominent strategy used by the teacher in three roles: as an academic instructor, a motivator, and a classroom manager. Positive politeness strategy was mostly used by the teacher in the role of being an evaluator. 134 students? utterances were also found. 78% of those utterances applied positive politeness strategy.Kata Kunci : four teacher?s roles, multicultural class, politeness strategies Penelitian ini bertujuan menyelidiki strategi kesantunan guru dalam empat peran guru dan menganalisis strategi kesantunan siswa dalam diskusi-diskusi kelas multikultural. Objek penelitian deskriptif kualitatif ini adalah ucapan-ucapan yang disampaikan oleh guru dan siswa dalam diskusi-diskusi kelas. Instrumen penelitian ini adalah peneliti yang mengumpulkan data melalui pengamatan dan wawancara. Data dikumpulkan dengan mengamati dan merekam video diskusi kelas, mengidentifikasi strategi kesantunan yang digunakan, serta mengelompokkan strategi kesantunan yang ditemukan. Data yang diperoleh dianalisis secara kualitatif melalui reduksi data, tampilan data, dan kesimpulan. Dalam penelitian ini, data ditampilkan dalam tabel dan dijelaskan melalui kutipan-kutipan dari percakapan yang terjadi dalam diskusi kelas. Ditemukan bahwa terdapat 496 ucapan guru yang digunakan berkaitan dengan strategi kesantunan. Bald on record adalah strategi yang paling sering digunakan guru dalam tiga peran, yakni sebagai instruktur akademik, motivator, dan pengelola kelas. Strategi kesantunan negatif paling banyak digunakan saat guru menjadi evaluator. Ditemukan pula 134 ucapan-ucapan siswa. 78% dari ucapan-ucapan tersebut menerapkan strategi kesantunan positif.keyword : empat peran guru, kelas multikultural, strategi kesantunan